Latent profiles of psychological wellbeing and psychological resources in Türkiye: tolerance, patience, compassion satisfaction, psychological flexibility - Kiye, Semra (Frontiers Media Sa, 2026)
Aims The aim of this study is to identify psychological wellbeing profiles based on the variables of tolerance, patience, compassion satisfaction, and psychological flexibility within the context of T & uuml;rkiye sample, and to examine whether these profiles differ across demographic subgroups.Sample The study was conducted with N = 513 voluntary participants living in T & uuml;rkiye.Method Data were collected using the Patience Scale, Compassion Satisfaction Scale, Tolerance Scale, Psychological Flexibility Scale, and Psychological Well-Being Scale. The construct validity of the scales was tested through confirmatory factor analysis (CFA), and the fit indices were found to be at acceptable levels. Internal consistency was confirmed using Cronbach's alpha coefficients. Latent profile analysis (LPA) was used to identify distinct psychological profiles. The relationship between participant profiles and socio-demographic variables was examined using the chi-square test.Results Considering parsimony and theoretical interpretability, a three-cluster solution was selected as the final model. The profiles corresponded to high, moderate, and low levels across all indicators and were labeled as High, Moderate, and Low Psychological Well-Being and Psychological Resources. Correlations among the variables were generally found to be moderately positive. After considering demographic variables, it was found that profiles with higher psychological wellbeing and psychological resources were associated with being female, married, and having a high level of education.Conclusion Overall, the findings suggest that psychological wellbeing in T & uuml;rkiye sample can be better understood through heterogeneous subgroups and provide insights for the design of culturally sensitive interventions and programs.
Keywords: Latent Profile Analysis; Psychological Wellbeing; Tolerance; Patience; Compassion Satisfaction; Psychological Flexibility